Comparative efficacy of operative versus conservative treatment for Rockwood type III acromioclavicular joint dislocation: a systematic review and meta-analysis of randomized controlled trials - Chengxin Xie; Shaohua Fan; Lin Chen; Lingqin Huang; Cong Chen; Hua Luo (BMC Musculoskeletal Disorders)
Abstract Background Optimal management of Rockwood type III acromioclavicular joint (ACJ) dislocation is still debated. Our aim is to conduct a meta-analysis of clinical studies evaluating the functional outcomes of operative versus conservative treatment for Rockwood type III ACJ dislocation. Methods We conducted a systematic search across PubMed, EMBASE, Web of Science, and the Cochrane Library, including only randomized controlled trials (RCTs) focusing exclusively on type III ACJ dislocation. A total of 244 patients from four studies were included. Outcomes measured included Constant scores (CS), coracoclavicular distance (CCD), pain, and complication rates. Heterogeneity was assessed and managed to ensure robust conclusions. Results The pooled results showed no significant difference in long-term functional outcomes, measured by CS, between surgical and conservative treatments (MD: 4.82, 95% CI: -6.42 to 16.06, P = 0.400). Surgical treatment provided better early pain relief and superior CCD at all follow-up points but did not improve long-term outcomes. Complication rates were similar for both treatments, though surgical intervention had a higher incidence of posttraumatic osteoarthritis and hardware-related issues. Conservative treatment resulted in fewer complications and comparable long-term results. Conclusions Based on the evidence, while surgical treatment may offer early benefits in pain relief and CCD improvement, it does not enhance long-term functional outcomes and is associated with higher specific complication rates. Conservative treatment provides a viable alternative with fewer complications and similar long-term outcomes. These findings highlight the need for individualized treatment plans based on patient-specific factors and suggest further high-quality, long-term studies to refine management strategies for Type III AC joint dislocations.